Quack‐induced dermatitis: A case report of two dermatitis artefacta induced by quacks advise - Pudasaini, Prajwal; Adhikari, Sadiksha; Das, Kinnor; Gorai, Suraljit; Pamela, Ruri D. (Clinical case reports, 2024)
Key Clinical Message This report delineates two instances of dermatitis artefacta (DA), a psychodermatological condition marked by self‐induced or exacerbated skin lesions. These cases, triggered by treatments from non‐qualified practitioners, highlight the critical need for healthcare professionals to discern the potential repercussions of unsound medical guidance. Quack‐induced dermatitis artefacta